Role of Behavioral Economics in Predicting Life Insurance Policy Lapses in United Kingdom - Christopher, Harry (Journal of Statistics and Actuarial Research, 2024)
Purpose: The aim of the study was to analyze the role of behavioral economics in predicting life insurance policy lapses in United Kingdom. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: In the United Kingdom, behavioral economics plays a significant role in predicting life insurance policy lapses. Key factors such as loss aversion, present bias, and financial literacy heavily influence policyholder decisions. Policyholders who are more loss-averse tend to maintain their policies, while those with a strong present bias are more likely to lapse, especially during financial stress. Additionally, lower financial literacy contributes to higher lapse rates, as individuals struggle to understand the long-term benefits of life insurance. Unique Contribution to Theory, Practice and Policy: Prospect theory, hyperbolic discounting & theory of planned behavior (TPB) may be used to anchor future studies on the role of behavioral economics in predicting life insurance policy lapses in United Kingdom. Insurers should tailor their communication strategies to address specific behavioral biases identified in policyholders. Policymakers should mandate the inclusion of financial literacy programs within the life insurance industry to educate consumers about the importance of maintaining their policies.